PERAN PERATURAN DAERAH DALAM MENCAPAI TUJUAN DESENTRALISASI - Fitriana, Mia Kusuma (Al-Qisth Law Review, 2017)
In the context of the implementation of autonomy and duty of assistance, local government shall have the right to form a regional regulation. Implementation of Regional Autonomy and Decentralization requires a legal instrument to ensure the implementation of the rights, powers and tasks of assistance which have been submitted by the Central Government to the Region. The legal instrument is in the form of a Regional Regulation. In the context of regional autonomy, the existence of local regulations in principle has a role to maximize decentralizationTo build local political infrastructure and superstructure to become more democratic, the creation of local government bureaucracy that can maximize the value of effectiveness, efficiency, equality and economics and ultimately can improve the welfare of the community as a whole to be deeper in both the necessary Local Regulations that will organize arrangements in the framework of the implementation of regional autonomy and co-administration, organizing the arrangement as a further elaboration of the higher legislation with due regard to the characteristics of each region, organizing the arrangement of things that are not contrary to the public interest and the enforcement of the arrangement of things that are not. Contrary to higher legislation. Thus the implementation of the optimization of decentralization objectives can be achieved by the formation of local regulations